2021
DOI: 10.3390/ijerph182212040
|View full text |Cite
|
Sign up to set email alerts
|

Stress Impact of COVID-19 Sports Restrictions on Disabled Athletes

Abstract: The stress impact of COVID-19 restrictions has put the adapted sports community at an unprecedented level of emergency. The self-report Event Scale—Revised (IES-R) questionnaire was administered to assess the level of psychological distress and emotive reactions such as intrusion (INT), avoidance (AV) and hyperarousal (HYP) following training and competitions suspension within a sample of Italian disabled athletes. A total of 146 self-selected volunteers were included in this study: 73 disabled athletes (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…Regarding competitive athletes, the first period of the pandemic quarantine impacted the planning and scheduling of athletes’ routines [ 3 ]. Canceled or postponed events and limited access to facilities affected both performance and psychological aspects, increasing distress [ 4 , 5 ]. The problems linked to the pandemic restrictions involved both athletes worried about their sport career concerns and managers for financial aspects [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding competitive athletes, the first period of the pandemic quarantine impacted the planning and scheduling of athletes’ routines [ 3 ]. Canceled or postponed events and limited access to facilities affected both performance and psychological aspects, increasing distress [ 4 , 5 ]. The problems linked to the pandemic restrictions involved both athletes worried about their sport career concerns and managers for financial aspects [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies have dealt with the impact of COVID-19 on mental health and psychological variables among para-athletes/athletes with disabilities ( Clemente-Suárez et al, 2020 ; Dehghansai et al, 2021 ; Fiorilli et al, 2021 ; Hu et al, 2021 ; Kaneda et al, 2021 ; Kubosch et al, 2021 ; Martínez-Patiño et al, 2021 ; Busch et al, 2022 ). These populations have had to experience unique challenges during the COVID-19 pandemic, which has been “a tale of two stories”: the infectious outbreak and disability.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in line with Martínez-Patiño et al (2021) , Fiorilli et al (2021) conducted a questionnaire-based, case-control study in Italy and recruited a sample of 146 athletes (73 without and 73 with disabilities, aged 42.11 ± 13.70 years). The authors found a lower subjective distress level among athletes with disabilities compared to their able-bodied counterparts (8.22% versus 30.14%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations